2020
DOI: 10.2196/19116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Multifaceted Wearable-Based Program for People With Knee Osteoarthritis: Randomized Controlled Trial

Abstract: Background Current guidelines emphasize an active lifestyle in the management of knee osteoarthritis (OA), but up to 90% of patients with OA are inactive. In a previous study, we demonstrated that an 8-week physiotherapist (PT)-led counseling intervention, with the use of a Fitbit, improved step count and quality of life in patients with knee OA, compared with a control. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 41 publications
2
46
0
1
Order By: Relevance
“…We conducted a cross-sectional cohort study using baseline data from 2 randomized clinical trials studying the effect of physical activity counseling for people with knee OA (SuPRA study), or RA or SLE (The Effectiveness of Physical Activity Monitoring in Inflammatory Arthritis [OPAM-IA] study) (33,34). Participants were eligible if they had a physician diagnosis of RA, SLE, or knee OA, or, in the case of undiagnosed knee OA, were age ≥50 years and had experienced pain or discomfort in or around the knee during the previous year lasting ≥28 days (35).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a cross-sectional cohort study using baseline data from 2 randomized clinical trials studying the effect of physical activity counseling for people with knee OA (SuPRA study), or RA or SLE (The Effectiveness of Physical Activity Monitoring in Inflammatory Arthritis [OPAM-IA] study) (33,34). Participants were eligible if they had a physician diagnosis of RA, SLE, or knee OA, or, in the case of undiagnosed knee OA, were age ≥50 years and had experienced pain or discomfort in or around the knee during the previous year lasting ≥28 days (35).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were eligible if they had a physician diagnosis of RA, SLE, or knee OA, or, in the case of undiagnosed knee OA, were age ≥50 years and had experienced pain or discomfort in or around the knee during the previous year lasting ≥28 days (35). Participants had to be able to participate in physical activities without health professional supervision, have no prior experience with using wearable activity monitors, and have email and internet access (33,34). Participants were recruited from facilities offering arthritis care in 2 large metropolitan health care authorities in British Columbia, Canada.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of clinical manifestation, it is mainly characterized by repeated and progressive pain and swelling of the joint, along with joint deformities and movement disorders. 12 The etiology of OA is not yet fully understood. 13 In recent years, accumulative studies have shown that various cytokines play important roles in the occurrence and development of OA, which are closely associated with the functional changes of synovium, articular cartilage, and subchondral cartilage.…”
Section: Discussionmentioning
confidence: 99%